Photodynamic Effects of Thuja occidentalis on Lung Cancer Cells - Loonat, Ayesha; Chandran, Rahul; Pellow, Janice; Abrahamse, Heidi (Frontiers in Pharmacology, 2022)
The global incidence and mortality rates resulting from lung cancer encapsulates a need to identify more effective treatment protocols. Photodynamic therapy (PDT) and homeopathy offer possible anticancer therapies as part of a multi-disciplinary approach. Studies have identified the anticancer effects of Thuja occidentalis Linn plant extracts. The aim of this study was to investigate the effects of Thuja occidentalis (TO) homeopathic mother tincture and TO mediated PDT (TO-PDT) on A549 lung cancer cells. Commercially available A549 cells were pre-treated with TO, or laser irradiation at 660 nm, or the combined treatment (TO-PDT). Cells were analyzed morphologically by inverted light microscopy and Hoechst stain; and biochemically by lactate dehydrogenase (LDH), adeno-sine triphosphate (ATP), and trypan blue assays. Cells treated with TO and TO-PDT demonstrated morphological changes in the cell and cell nuclei indicative of cell death. These groups exhibited a dose dependent increase in LDH release and a decrease in ATP levels and cell viability indicating its cytotoxic and antiproliferative potential. Furthermore, at the same doses, TO when photoactivated in PDT induced enhanced anticancer responses thereby surpassing the effects of treatment with the tincture alone. Results demonstrate how the direct cytotoxic effects of TO can be improved when administered as a photosensitizer in PDT to promote cancer cell death.